TRACHYPENAEOPSIS MINICOYENSIS SP. NOV. (PENAETDAE, DECAPODA) FROM THE LACCADIVE SEA - Thomas, M M (Indian Journal of Fisheries, 2011)
The genus Trachypenaeopsis Burkenroad is reported for the lirst time from the Indian Region and a new species T. minicoyensis collected from Minicoy Island, Laccadive Archipelago, is described in detail. The present species differs from other known species viz., T. richtersii (Miers) and T. mobillspinis (Rathbun) in the structure ot the petasma, thelycum and telson. A key to the identification of the known species of the genus is also provided.